2005
DOI: 10.15288/jsa.2005.66.185
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial, cultural and genetic influences on alcohol use in Asian American youth.

Abstract: Objective-Environmental and cultural factors, as well as a genetic variant of the aldehyde dehydrogenase gene (the ALDH2*2 allele) have been identified as correlates of alcohol use among Asian Americans. However, concurrent examination of these variables has been rare. The present study assessed parental alcohol use, acculturation and ALDH2 gene status in relation to lifetime, current and heavy episodic drinking among Chinese and Korean American undergraduates.Method-Participants (N = 428, 51% women; 52% Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 61 publications
(97 reference statements)
6
50
0
Order By: Relevance
“…Whereas most studies suggest that acculturation is a risk factor for alcohol use among Asian Americans, the present findings suggest that protective effects may also exist and may vary by ethnic subgroup. Another study of college students found evidence that acculturation was a risk factor for heavy episodic drinking among Chinese Americans but not Korean Americans (Hendershot et al, 2005). Collectively, findings from that and the current study suggest that acculturation's influence on drinking behavior can vary in these two groups, with risk and protective influences being more evident among Chinese Americans and Korean Americans, respectively.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Whereas most studies suggest that acculturation is a risk factor for alcohol use among Asian Americans, the present findings suggest that protective effects may also exist and may vary by ethnic subgroup. Another study of college students found evidence that acculturation was a risk factor for heavy episodic drinking among Chinese Americans but not Korean Americans (Hendershot et al, 2005). Collectively, findings from that and the current study suggest that acculturation's influence on drinking behavior can vary in these two groups, with risk and protective influences being more evident among Chinese Americans and Korean Americans, respectively.…”
Section: Discussionsupporting
confidence: 53%
“…Some studies allow global inferences about acculturation's effects by comparing the drinking rates of U.S. Asians to their counterparts abroad (e.g., Higuchi et al, 1994;Johnson et al, 1987;Park et al, 1984;Yamamoto et al, 1994); however, these studies typically have not measured acculturation directly. Several studies of Asian Americans show that measured indices of acculturation correlate positively with drinking quantity/frequency (Hahm et al, 2003(Hahm et al, , 2004Hendershot et al, 2005;Nakashima and Wong, 2000;Nakawatase et al, 1993;Song et al, 2004;Sue et al, 1979). Most studies have assessed acculturation using unidimensional indicators such as place of birth, length of residency, or language.…”
mentioning
confidence: 99%
“…The same pattern was not true for females. Other studies have shown that greater acculturation is associated with greater substance use in Asian American college students (Hendershot, MacPherson, Myers, Carr, & Wall, 2005;So & Wong, 2006).…”
Section: Racementioning
confidence: 92%
“…Because the procedure used and the small sample size limited the number of matching variables that could be considered, groups were compared on additional variables potentially related to alcohol use progression, including aldehyde dehydrogenase metabolizing enzyme (ALDH2) status and acculturation (Doran et al, 2007), parental alcohol dependence, peer smoking, and baseline past-14-day HDE. Although none of these variables differed signifi cantly across groups in the present study (Table 2), given the small sample size (and therefore limited statistical power), we chose to include ALDH2 (p = .42) and acculturation (p = .06) as covariates in the primary analyses of alcohol outcomes because these represent ethnic-specifi c variables that have been associated with alcohol use in other studies (Doran et al, 2007;Hendershot et al, 2005;Luczak et al, 2004).…”
Section: Matchingmentioning
confidence: 99%